Pain treatment and functional improvement in home health care: Relationship with dementia. Issue 12 (21st August 2021) - Wang, Jinjiao; Cato, Kenrick; Conwell, Yeates; Yu, Fang; Heffner, Kathi; Caprio, Thomas V.; Nathan, Kobi; Monroe, Todd B.; Muench, Ulrike; Li, Yue
Abstract: Background: Pain management is important to post‐acute functional recovery, yet older persons with Alzheimer's disease and related dementias (ADRD) are often undertreated for pain. The main objectives were (1) to examine the relationship between ADRD and analgesic use among Medicare home health care (HHC) recipients with daily interfering pain, and (2) to examine the impact of analgesic use on functional outcome in patients with and without ADRD. Methods: We analyzed longitudinal data from the Outcome and Assessment Information Set, Medicare HHC claims, and HHC electronic medical records during a 60‐day HHC episode. The sample included 6048 Medicare beneficiaries ≥65 years receiving care from an HHC agency in New York in 2019 who reported daily interfering pain. Analgesic use was assessed during HHC medication reconciliation and included any analgesic, non‐opioid analgesic, and opioid. ADRD was identified from ICD‐10 codes (HHC claims) and cognitive impairment symptoms (Outcome and Assessment Information Set [OASIS]). Functional outcome was measured as change in the composite Activity of Daily Living (ADL) limitation score in the HHC episode. Results: ADRD was related to a lower likelihood of using any analgesic (odds ratio [OR] = 0.66, 95% confidence interval [CI]: 0.49, 0.90, p  = 0.008) and opioids (OR = 0.54, 95% CI: 0.47, 0.62, p  < 0.001), but not related to non‐opioid analgesic use (OR = 0.94, 95% CI: 0.74, 1.18, p  = 0.58). Stratified analyses showed that any analgesic use ( β  = −0.43, 95% CI: −0.73, −0.13, p  = 0.004) and non‐opioid analgesic use ( β  = −0.31, 95% CI: −0.56, −0.06, p  = 0.016) were associated with greater ADL improvement in patients with ADRD, but not in patients without ADRD. Opioid use was not significantly related to ADL improvement regardless of ADRD status. Conclusions: HHC patients with ADRD may be undertreated for pain, yet pain treatment is essential for functional improvement in HHC. HHC clinicians and policymakers should ensure adequate pain management for older persons with ADRD for improved functional outcomes.